HUBUNGAN LINGKUNGAN BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS V SDN 102028 KAMPUNG GELAM KABUPATEN SERDANG - WARUWU, YENIMA (Jurnal Ilmiah Aquinas, 2018)
This study is a quantitative study with a population of 129 students ingrade V SDN 102028 Kampung Gelam district of Serdang Bedagai with the number of respondents as many as 27 people. Data collection techniques used were questionnaires, documentation, and interviews. Student learning outcomes are influenced by various factors that occur in the learning process both internally and externally. One of the external factors that play a role in determining the success of student learning is the learning environment of family, school and community. Of the three learning environments concerned about how parents support children's learning, the facilities at school for learning activities and how students interact with others. Without the support of these three things, will make the learning process becomes hampered. Data analysis technique used is descriptive analysis technique while hypothesis test using product moment correlation test assisted by program of SPSS version 21. Based on the results of research, learning environment and student learning outcomes in general are in enough categories. Hypothesis test with a significance level of 5% obtained results indicating that the school environment is positively and significantly correlated with student learning outcomes. Shown by the result of analysis of rhitung is bigger than rtabel (0,504> 0,381) and coefficient of determination 25%.It can be concluded that between the learning environment and the learning outcomes have a positive and significant relationship. The results of this study are expected to be useful for students, parents, students, and principals. Proposed suggestion is that the learning environment should be created safely and comfortably so that the students' learning result will be optimal.